2023
DOI: 10.3390/ma16165558
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caries around Restoration by Ion-Releasing Restorative Materials: An In Vitro Optical Coherence Tomography and Micro-Computed Tomography Evaluation

Abstract: The objective of this study was firstly to assess the demineralization inhibitory effect of ion-releasing restorations in enamel adjacent to restoration using a biofilm caries model and secondly to compare the effect to that in a chemical caries model. Fifty-six bovine incisors were filled with either Surefil one (SuO), Cention N (CN) (both ion-releasing materials), Ketac-Molar (GIC) or Powerfill resin composite (RC). The restored teeth were then randomly divided into 2 groups according to the used caries mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The lesion depth, integrated reflectivity, and attenuation coefficients are among the quantitative outcome measures that are often utilized [18][19][20][21]27,28]. The relative changes of these outcome measures for enamel and dentin before and after an intervention, be it demineralization or remineralization, can be used to assess the effect of that intervention [29,30]. However, variations in these quantitative results between different studies have been found, and this has been attributed to the different OCT systems used, sample preparation methods, and the arbitrary nature of some of the outcome measures [31].…”
Section: Introductionmentioning
confidence: 99%
“…The lesion depth, integrated reflectivity, and attenuation coefficients are among the quantitative outcome measures that are often utilized [18][19][20][21]27,28]. The relative changes of these outcome measures for enamel and dentin before and after an intervention, be it demineralization or remineralization, can be used to assess the effect of that intervention [29,30]. However, variations in these quantitative results between different studies have been found, and this has been attributed to the different OCT systems used, sample preparation methods, and the arbitrary nature of some of the outcome measures [31].…”
Section: Introductionmentioning
confidence: 99%